Aristolactams and further constituents from Aristolochia chamissonis - Tsuruta, A. Y. (2002)
From the ethanol extract of the stems of Aristolochia chamissonis, spathulenol, sitosterol, beta-sitosteryl-D-glucoside, kolavelool, 13-epi-2-xo-kolavelool, trans-M-p-coumaroyltyramine, allantoin, aristolochic acid I, and aristolactam All were isolated. The structures of aristolactam All and piperolactam A have been revised by means of spectroscopic methods and chemical derivatizations.